β-Arrestin1 Reduces Oxidative Stress via Nrf2 Activation in the Rostral Ventrolateral Medulla in Hypertension - Tan, Xing; Jiao, Pei-Lei; Sun, Jia-Cen; Wang, Wen; Ye, Peng; Wang, Yang-Kai; Leng, Yue-Qi; Wang, Wei-Zhong (Frontiers in Neuroscience, 2021)
Oxidative stress in the rostral ventrolateral medulla (RVLM), a key region for blood pressure (BP) regulation, has been demonstrated to be responsible for the overactivity of the sympathetic nervous system in hypertension and heart failure. The nuclear factor-erythroid-2-related factor 2 (Nrf2) is a key transcription factor that maintains redox homeostasis by governing a broad array of antioxidant genes in response to oxidant stress. β-arrestin1 is a multifunctional scaffold protein with the ability to interact with diverse signaling molecular independent of G protein coupled receptors, and its overexpression in the RVLM could reduce BP and renal sympathetic nerve activity (RSNA) in spontaneously hypertensive rats (SHR). The goal of this study was to investigate whether Nrf2-mediated anti-oxidative stress is involved in the antihypertensive effect of β-arrestin1 in the RVLM. It was found that the activation level of Nrf2 in the RVLM of SHR was significantly reduced, compared with normotensive WKY rats. Overexpression of β-arrestin1 in the RVLM significantly decreased ROS production and facilitated the Nrf2 activation in the RVLM of SHR, accompanied by up-regulating the expression of HO-1 and NQO-1. However, Nrf2 knockdown attenuated the antioxidant effect of β-arrestin1 overexpression in the RVLM by down-regulating HO-1 and NQO-1 expression levels. In conclusion, the current results suggested that the antihypertensive effect of β-arrestin1 overexpression in the RVLM is mediated by decreased ROS production, which is associated with Nrf2 activation.